Associations of Morphological Changes in Skeletal Muscles of Preschool Children in China Following Physical Activity - Pengyu Deng; Hayao Ozaki; Toshiharu Natsume; Dandan Ke; Dajiang Lu; Koya Suzuki; Hisashi Naito (MDPI AG, 2023)
Purpose: Physical activity (PA) is likely to be the most important modifiable factor in skeletal muscle development. However, the influence of PA on the skeletal muscle of preschool children has not been thoroughly investigated. The main objective of this study was to quantitatively measure PA, and then, to assess whether associations exist between site-specific muscle changes and PA in relation to sex and weight statuses in preschool children aged 3 to 4 years. Methods: A total of 86 healthy preschool children, aged 3-4 years, were instructed to wear an accelerometer for seven consecutive days. The number of steps taken daily, and minutes spent in moderate-vigorous PA (MVPA) and total PA (TPA) were recorded. Muscle thickness was measured by B-mode ultrasonography using a 5-18 MHz scanning head. Muscle thickness was measured at seven sites: the lateral forearm, upper arm, abdomen, anterior and posterior thigh, and anterior and posterior lower leg. Results: There was no significant difference between boys and girls in terms of MVPA and TPA on weekdays and weekends. According to the linear regression models, after adjusting for daylight duration, the muscle of the posterior thigh was significantly positively associated (p < 0.05) with daily steps and MVPA on weekdays for boys and girls, respectively. Conclusions: We found that the muscle thickness of the posterior thigh in preschool children was significantly positively associated with PA, as measured by daily steps and MVPA. We suggest that for the overall health and well-being of preschool children, the levels of PA should be maintained and/or increased, and preferably transformed into a regular part of daily living.